Pharmacological Validation of Long-Term Treatment with Antiretroviral Drugs in a Model of SIV-Infected Non-Human Primates - Thibaut Gelé; Hélène Gouget; Nathalie Dereuddre-Bosquet; Valérie Furlan; Roger Le Grand; Olivier Lambotte; Delphine Desjardins; Aurélie Barrail-Tran (MDPI AG, 2022)
The development of animal models undergoing long-term antiretroviral treatment (ART) makes it possible to understand a number of immunological, virological, and pharmacological issues, key factors in the management of HIV infection. We aimed to pharmacologically validate a non-human primate (NHP) model treated in the long term with antiretroviral drugs after infection with the pathogenic SIVmac251 strain. A single-dose pharmacokinetic study of tenofovir disoproxil fumarate, emtricitabine, and dolutegravir was first conducted on 13 non-infected macaques to compare three different routes of administration. Then, 12 simian immunodeficiency virus (SIV)-infected (SIV+) macaques were treated with the same regimen for two years. Drug monitoring, virological efficacy, and safety were evaluated throughout the study. For the single-dose pharmacokinetic study, 24-h post-dose plasma concentrations for all macaques were above or close to 90% inhibitory concentrations and consistent with human data. During the two-year follow-up, the pharmacological data were consistent with those observed in humans, with low inter- and intra-individual variability. Rapid and sustained virological efficacy was observed for all macaques, with a good safety profile. Overall, our SIV+ NHP model treated with the ART combination over a two-year period is suitable for investigating the question of pharmacological sanctuaries in HIV infection and exploring strategies for an HIV cure.